Geometric methods used in the construction of architectural forms (Journal of Architectural Design, 2022)
All the architectural forms applied in modern construction use geometric shapes. Therefore, it is not good for a builder to start construction without mastering geometry. This article presents a brief overview on how to build some architectural shapes from geometric shapes.